The Role of Domestic Factors in the EU’s Governance of Labour Standards through Trade - Franklin Maduko; Pal, Timea; László Bruszt (The Role of Domestic Factors in the EU’s Governance of Labour Standards through Trade, 2020)
This paper analyses the role of domestic factors in the ability of the EU to promote NTPOs through formal trade policies and market integration, as two distinct governance approaches. Focusing on labour standards, we examine how economic and political factors in developing economies influence the ability of key stakeholders – governments, businesses and labour organizations – to undermine or reinforce EU governance efforts. We use a combination of regression and comparative case analysis to assess associations and understand processes on ground. The quantitative analysis shows that improvements in labour standards are closely associated with 1) labour standards in key export markets, 2) technological sophistication of exports, 3) state capacity and 4) freedom of CSOs. Comparative analysis of how differences in state strategies and capacity, key export destinations and strength of labour organizations across Moldova and Morocco set in place divergent pathways of labour standard improvements allows us to shed more light on the potentials and limitations of EU governance efforts.